Engagement Project: elements for a reformulation of the Tutorial Action Plan of the Teacher Training degrees at the University of Barcelona - Calderón-Garrido, Diego; Gustems-Carnicer, Josep; Arús, Maria-Eugènia; Ayuste-González, Ana; Batalla, Albert; Calderón, Caterina; Castell, Julia; Elgstrom, Edmon; Fons, Montserrat; Kieling, Martina; Kirchner, Teresa; Martín, Carolina; et al. (Cultura y Educación, 2019)
As a teaching method, tutorials are fundamental to university education, and are underpinned by the following goals: to accompany students; to help them establish a clear training pathway; and to promote their academic achievement. Our proposal aims to introduce psychological aspects into the Tutorial Action Plan (TAP) which, while often left unattended, are closely related to academic achievement. Our objective is to identify the relation between the academic commitment of pre-service teachers (preschool education, primary education and double degree students) at the UB and stress and coping skills, academic motivation, achievement and self-efficacy, as well as the opinions of students and tutors on the resources used during TAP and potential improvements to it. This is a transversal prospective exploratory study, applying the following questionnaires: Academic commitment (UWESS-9); Perceived Stress Scale (PSS); Self-efficacy (NGSE); Motivation (MSLQ); and two ad hoc online questionnaires. In conclusion, we hope that the results of this study will help us reformulate the TAP of said degree programmes, improving personalized attention and the quality of the student tutorial system, which is one of the standards used to assess universities.
Proyecto Engagement: elementos para una reformulación del Plan de Acción Tutorial de los grados de maestro en la Universidad de Barcelona
La tutoría como función docente es un proceso fundamental en la universidad, que persigue las siguientes metas: acompañar, asesorar en la definición de un proyecto de formación, y facilitar el aprovechamiento académico del estudiante. Nuestra propuesta pretende introducir en el Plan de Acción Tutorial (PAT) aspectos psicológicos que se desatienden pero que guardan una estrecha relación con el rendimiento académico. Nuestro objetivo es conocer la relación entre el compromiso académico del alumnado de Maestro (Ed. Infantil, Primaria y doble titulación) en la UB, y el estrés y afrontamiento, motivación académica, rendimiento, y autoeficacia, así como la opinión del alumnado y docentes sobre recursos empleados y mejoras del PAT. Se trata de un estudio exploratorio prospectivo transversal, aplicando los siguientes cuestionarios: Compromiso académico (UWESS-9), Escala de Estrés Percibido (PSS), Autoeficacia (NGSE), Motivación (MSLQ) y dos cuestionarios on line ad hoc. En conclusión, esperamos que los resultados de esta investigación nos permita replantear el PAT de dichos grados, mejorar la atención personalitzada y calidad del sistema tutorial del alumno, uno de los estándares de acreditación en las evaluaciones de las universidades.
Keywords: academic commitment; tutorial action plan; higher education; teacher training; JCR; compromiso académico; plan de acción tutorial; educación superior; formación de maestros; Scopus